El papel de los medios digitales en la promoción de la salud en el Hospital Cantonal de la ciudad de Sangolquí: Propuesta de reportaje digital acerca de la promoción de la salud en el Hospital Cantonal de Sangolquí. - Asimbaya Pillajo, Darwin Miguel (2023)
The present research work was carried out through a significant analysis regarding the promotion of health in the city of Sangolquí, as such, the study focused on the development of two surveys, each one of them was directed to health professionals and patients at the Sangolquí hospital. In turn, within the results it was possible to denote that, although there is work around the promotion of health by the Hospital, there are no adequate means from which information is disseminated regarding the benefits derived from said Consequently, promotion is established as the central task of this work, the creation of a digital report proposal, in order to reach all citizens.